New Encapsulation of Fucoxanthin Isolated from Cyclotella striata by Nano Chitosan–Pectin using Ionic Gelation Method - Nahrowi, Ridho; Solehati, Siti; Widyastuti, Widyastuti; Juliasih, Ni Luh Gede Ratna; Pandiangan, Kamisah Delilawati; Setiawan, Andi; Hendri, John (Science and Technology Indonesia, 2024)
Fucoxanthin is an anticancer, antioxidant, antimicrobial, and anti-inflammatory bioactive compound. Unfortunately, the conjugated double bonds of the fucoxanthin structure make it unstable, posing issues for product development, particularly with regard to shelf life. This research study aims to synthesize nano chitosan–pectin and encapsulate isolated fucoxanthin by nano chitosan–pectin using an ionic gelation method. Fucoxanthin was obtained through isolation of microalgae species Cyclotella striata. The best result of nanoparticle size using a particle size analyzer was chitosan:pectin 1 : 2 of 172 nm. Fourier transform infrared analysis showed that there was an interaction between chitosan–pectin and fucoxanthin, which was characterized by a shift in the C O absorption fucoxanthin from 1736 to 1632 cm-1. The result of morphological analysis of nano chitosan–pectin–fucoxanthin using a scanning electron microscopeshows a spherical morphology with a size between 140 and 265 nm. The result of encapsulation efficiency was 75.18%, whereas encapsulation stability increased fucoxanthin oxidation half-life 4.7 times longer than that of unencapsulated fucoxanthin. The nano chitosan pectin could be utilized as a matrix conjugate to increase the stability of fucoxanthin significantly by encapsulation. This information is expected to be useful in developing encapsulation applications for unstable compounds.